Representasi Perempuan dalam Jabatan Struktural Birokrasi - Andayana, Made Ngurah Demi; Pradana, I Putu Yoga Bumi; Fallo, Adriana; Witin, Maria Wihelmina (Faculty of Social Science, Universitas Negeri Padang, 2023)
The purpose of this study was to explain the level of representation of women in bureaucratic, structural positions and the inhibiting factors they face in occupying bureaucratic, structural positions in East Flores Regency. The research method used is qualitative descriptive with interviews of 13 informants determined through purposive. The results of this study explain that in the last three years, the number of female civil servants in echelons II and III is less than that of men. In 2021, there were three female civil servants left because, in 2020, one of the female civil servants died. Furthermore, in 2022, one of the female civil servants finished her term. The inhibiting factors faced by women in bureaucratic, structural positions are viewed in two forms: 1) internal constraints such as lack of self-confidence and the multiple roles played by women, 2) external constraints related to a) constraints from the family, and b) constraints from society related to the value system and norms. The research is expected as input for East Flores Regency